Laser-based measurements for time and frequency domain applications : a handbook - Maddaloni, Pasquale; Bellini, Marco, 1964-; De Natale, Paolo (Boca Raton, Fla. : Taylor & Francis, 2013)
"Providing a self-contained introductory review of modern laser-based time and frequency measurement techniques, this text represents an interdisciplinary look at the recent developments and future directions of optical frequency meteorology, as well as a range of meteorological disciplines. Suitable for graduate students and practicing physicists and engineers, it discusses the most advanced laser-based spectroscopic measurement techniques, including UV, j1W, visible frequency, and IR laser. The authors, leading optical meteorologists, also cover advanced spectroscopic techniques, experimental quantum optics, and quantum information"--
Includes bibliographical references.
Description based on metadata supplied by the publisher and other sources.
Electronic reproduction. Santa Fe, Arg.: elibro, 2020. Available via World Wide Web. Access may be limited to eLibro affiliated libraries.
Keywords: Time measurements; Frequencies of oscillating systems -- Measurement; Lasers -- Scientific applications; Optical measurements; Spectrum analysis; Atmosphere -- Laser observations; Electronic books